Assessment of potential resistance to imidazolinone herbicide in three rice weed species - Razak, Nur Azrina (2015)
This experiment was conducted to examine the potential resistance of three rice weeds species, namely Cyperus iria, Echinochloa cruss-galli and Oryza sativa var sylvatica to imidazolinone herbicide. Different doses of imidazolinone herbicide (0, 0.275 g ai L-1. 0.55 g ai L-1, 1.10 g ai L-1 and 2.20 g ai L-1) were used as the treatment. The experiment was conducted in Randomized Completely Block Design (RCBD) with three replications. The parameters measured were amount of chlorophyll content, percentage of survival, fresh weight of roots and dry weight of roots. Data percentage of survival, root fresh weight and root dry weight were taken for 21 days after the treatments. Data were analysed by Analysis of Variance (ANOVA) using Statistical Analysis System (SAS) to test significance and the means were separated to Least Significant Difference (LSD). Plant survival (%) was subjected to a probit analysis by using the Statistical Software Package of SPSS in order to determine the LD50 (the amount of imidazolinone required for 50% death) value. At the recommended rate of imidazolinone, Cyperus iria had the highest percentage of weed survival which was 53%, followed by Echinochloa crus-galli (10%), while Oryza sativa var sylvatica was completely controlled by imidazolinone. LD50 for Cyperus iria also indicated the highest which was 3.178g ai L-1 compared to other weed species. This shows that Cyperus iria has the highest risk of potential resistant towards imidazolinone herbicide.